Is prostate brachytherapy a dying art? Trends and variation in the definitive management of prostate cancer in Ontario, Canada. (November 2020) - Corkum, Mark T.; Morton, Gerard; Louie, Alexander V.; Bauman, Glenn S.; Mendez, Lucas C.; Chin, Joseph; D'Souza, David P.; Dinniwell, Robert E.; Velker, Vikram M.; Saskin, Refik; Warner, Andrew; Rodrigues, George B.
Highlights: Between 2007-2017, prostate brachytherapy (BT) use increased in Ontario, Canada. A greater increase in BT boost compared to BT monotherapy was observed. If the first radiation oncologist seen performed BT, patients received BT more often. Substantial regional, provider and patient variation were observed. Abstract: Background and purpose: Declining prostate brachytherapy utilization has been reported in several studies, despite strong evidence for efficacy and safety compared to alternatives. We sought to evaluate contemporary trends in brachytherapy, external beam radiotherapy (EBRT) and prostatectomy utilization in a publicly funded healthcare system. Materials and methods: Men with localized prostate cancer diagnosed and treated between 2006 and 2017 in Ontario, Canada were identified using administrative data. Men received EBRT, brachytherapy (monotherapy or boost) or prostatectomy as initial definitive management. Multivariable logistic regression evaluated patient-, tumour-, and provider-factors on treatment utilization. Results: 61, 288 men were included. On multivariable regression, the odds of receiving brachytherapy boost increased 24% per year (odds ratio [OR]:1.24, 95% CI 1.22–1.26, p  < 0.01), brachytherapy monotherapy increased 3% per year (OR:1.03, 95% CI:1.02–1.04, p  < 0.01), and prostatectomy declined by 6% per year (OR:0.94, 95% CI 0.93–0.95, p  < 0.01). Treatment year was not significant on multivariable modelling of EBRT. In a separate multivariable model limited to those who received radiotherapy, if the first radiation oncologist seen performed brachytherapy, the OR of receiving brachytherapy monotherapy over EBRT was 5.66 (95% CI: 5.11–6.26, p  < 0.01) and 2.88 (95% CI: 2.60–3.19, p  < 0.01) for brachytherapy boost over EBRT alone. Substantial geographic, provider and patient variation in treatment receipt was observed. Conclusion: We found increasing brachytherapy utilization, largely driven by increasing utilization of brachytherapy boost. To our knowledge, this is the first report of increasing brachytherapy use in the era of dose escalated EBRT.